2007
DOI: 10.1088/1741-2560/4/1/s01
|View full text |Cite
|
Sign up to set email alerts
|

Responses of ganglion cells to repetitive electrical stimulation of the retina

Abstract: Retinal ganglion cells (RGCs) can be activated electrically either directly or indirectly (via the retinal neural network). Previous studies have shown that RGCs can follow high stimulus rates (> or = 200 pulses s(-1)) when directly activated. In the present study, we investigated how well RGCs can follow repetitive stimulation of the neural network. We studied the responses (spike activity) of RGCs in isolated rabbit retina to stimulation with paired pulses applied at different interpulse intervals and trains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
99
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 19 publications
16
99
2
Order By: Relevance
“…Changes in neural activities responding to repetitive stimulation by pulse trains applied with various inter-pulse intervals were observed. The results showed that the response strength of the RGCs of rd1 mice could be effectively modulated by inter-pulse interval, and, thus, by pulse frequency, as previously shown for normal retina (Jensen and Rizzo, 2007). An optimal range for the pulse frequency modulation was presently determined by observing the frequency ranges where the RGC response strength was increased monotonically by pulse frequency.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Changes in neural activities responding to repetitive stimulation by pulse trains applied with various inter-pulse intervals were observed. The results showed that the response strength of the RGCs of rd1 mice could be effectively modulated by inter-pulse interval, and, thus, by pulse frequency, as previously shown for normal retina (Jensen and Rizzo, 2007). An optimal range for the pulse frequency modulation was presently determined by observing the frequency ranges where the RGC response strength was increased monotonically by pulse frequency.…”
Section: Introductionsupporting
confidence: 78%
“…RGC responses to repetitive stimulation pulses have been reported for normal retinas (Fried et al, 2006;Sekirnjak et al, 2006;Jensen and Rizzo, 2007;Ahuja et al, 2008). However, few reports have described RGC responses of degenerated retinas evoked by repetitive pulse stimulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such stimulation attempts use much larger electrodes (125-500 m) and/or long-duration stimulation pulses (ϳ1 ms), and result in multiple evoked spikes at long latencies (ϳ10 ms). With these stimulation configurations, spike thresholds are typically much higher than the direct-activation values reported in this study (Jensen et al, 2003;Suzuki et al, 2004;Guven et al, 2005;Jensen and Rizzo, 2007;Ye and Goo, 2007). Results from the present study are most comparable with recently published reports of epiretinal stimulation that activated ganglion cells directly by using small electrodes and short pulses: 0.05-0.31 mC/cm 2 for 40 m disk electrodes in frog retina (Kuras et al, 2004), 0.14 -0.25 mC/cm 2 for 30 m cone-shaped electrodes in rabbit retina (Fried et al, 2006), and 0.02-0.20 mC/ cm 2 for 8 -12 m disk electrodes in rat retina (Sekirnjak et al, 2007).…”
Section: Low Stimulation Thresholdsmentioning
confidence: 55%
“…Several groups have targeted deeper retinal neurons (bipolar cells and photoreceptors) for epiretinal stimulation, which activates ganglion cells through the retinal neural network and thus stimulates them indirectly (Jensen and Rizzo, 2007). Such stimulation attempts use much larger electrodes (125-500 m) and/or long-duration stimulation pulses (ϳ1 ms), and result in multiple evoked spikes at long latencies (ϳ10 ms).…”
Section: Low Stimulation Thresholdsmentioning
confidence: 99%